(3GdHMK hGdJMbjb aj LQGFe GdGZJUGH (B=s Rape crimes investigation - (3YHO GdeWdH, eeOhM YHO GdMejO,s 1955- ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3TQWI GdTGQbI, eQcR HMhK GdTQWI,s, 2006)
(3jJfGhd cJGH (B((3GdHMK hGdJMbjb aj LQGFe GdGZJUGH(B) (3hGdPj bGe HJCdjag (B((3eeOhM YHO GdMejO YHO GdeWdH(B) (3aj MhGdj (B(95) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3LQGFe GdGZJUGH(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdeHMK GdChd (B: (3JUfja GdLQGFe GdLfSjI hLQGFe GdGZJUGH GdebJQf HGdbJd, GdeHMK GdKGfj (B: (3GdJMbjbGJ GdeJYdbI HGdGZJUGH, GdeHMK GdKGdK (B: (3LeY GdCOdI GdeJYdbI HGdGZJUGH(B.s
(3HHdjhLQGajI (B: (3UaMI (B94-95.s
(3jTJed Ydi edNU HGddZJjf GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdGZJUGHs; (3GdLQGFe GdLfSjIs; (3GdHMK GdLfGFjs; (3GdJMbjb GdLfGFjs